Cellulose-based technologies for pollutant removal from wastewater: A bibliometric review - Wan Norfazilah, Wan Ismail; Nurul Huda, Abu Bakar; Nor Adila, Mhd Omar; Khairiah, Mohd Mokhtar; Nurul Hidayah, Abu Bakar (Springer Netherlands, 2025)
The growing demand for sustainable wastewater treatment emphasizes the need for eco-friendly and cost-effective solutions. This study addresses a gap in the literature by examining the role of cellulose-based materials in adsorbing pollutants such as heavy metals, synthetic dyes, and organic compounds. A bibliometric analysis was performed using VOSviewer on 730 research articles published between 2014 and 2024, sourced from the Scopus database. The analysis focused on citation patterns, bibliographic coupling, and co-occurrence mapping to identify trends in pollutant removal mechanisms, factors affecting treatment efficiency, and the application of cotton-waste adsorbents. The findings reveal three primary research clusters and highlight the significant potential of cellulose-based adsorbents for wastewater treatment. The cellulose-based materials not only offer a more sustainable solution but also contribute to reducing costs and promoting the circular economy through the repurposing of cotton or fabric waste. The study establishes cellulose-derived adsorbents as promising alternatives to conventional materials, offering a pathway for improving environmental sustainability, reducing the burden on landfills, and advancing waste management practices. It also highlights the related technologies in addressing global pollution challenges.